2012
DOI: 10.1371/journal.pone.0034356
|View full text |Cite
|
Sign up to set email alerts
|

The Group Delay and Suppression Pattern of the Cochlear Microphonic Potential Recorded at the Round Window

Abstract: BackgroundIt is commonly assumed that the cochlear microphonic potential (CM) recorded from the round window (RW) is generated at the cochlear base. Based on this assumption, the low-frequency RW CM has been measured for evaluating the integrity of mechanoelectrical transduction of outer hair cells at the cochlear base and for studying sound propagation inside the cochlea. However, the group delay and the origin of the low-frequency RW CM have not been demonstrated experimentally.Methodology/Principal Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 41 publications
(41 reference statements)
6
35
0
Order By: Relevance
“…For low frequency tones, however, the phase locking from auditory nerve fibers (i.e., auditory neurophonic) may contribute to the response (Henry, 1995;Lichtenhan et al, 2012). In gerbil, Henry (1995) and others (He et al, 2012) showed that the auditory neurophonic contributes to the recording at the round window for lowfrequency tones presented at low signal levels. At high signal levels such as 80 dB SPL, a difference between responses with and without TTX is not observable.…”
Section: Discussion a Assumptionsmentioning
confidence: 99%
“…For low frequency tones, however, the phase locking from auditory nerve fibers (i.e., auditory neurophonic) may contribute to the response (Henry, 1995;Lichtenhan et al, 2012). In gerbil, Henry (1995) and others (He et al, 2012) showed that the auditory neurophonic contributes to the recording at the round window for lowfrequency tones presented at low signal levels. At high signal levels such as 80 dB SPL, a difference between responses with and without TTX is not observable.…”
Section: Discussion a Assumptionsmentioning
confidence: 99%
“…The first is that the literature suggests that a significant proportion of the RW response is generated from auditory nerve potentials in addition to OHCs, especially for low-frequency stimuli (Henry, 1995; Patuzzi et al, 1989; He et al, 2012; Lichtenhan et al, 2014). In order to quantify the proportion of neural and OHC potentials present in the RW response, or cochlear response (CR), Chertoff et al (2014) damaged the auditory nerve with 10 mM of an ototoxic drug, ouabain, and recorded the CR before and after an acute application to the RW niche.…”
Section: Introductionmentioning
confidence: 99%
“…If basilar membrane displacement to a low frequency tone is not everywhere constant and in phase along the cochlear spiral, electrical responses of differing polarity from many cells will sum and consequently smooth the amplitude of the cochlear response. Moreover, slow biasing of cochlear mechanics with a low-frequency tone has largely ignored the contribution of neural excitation that is predominately phase locked to low-frequency tones (Henry, 1995;He et al, 2012;Lichtenhan et al, 2014;Stankovic and Guinan, 1999). That is to say, low frequency tones evoke both hair cell and neural responses.…”
Section: Introductionmentioning
confidence: 99%